Clinical review and drug sensitivity test of Corynebacterium kroppenstedtii complex isolates in non-lactating patients with severe mastitis - Liang, Zuxin; Zeng, Zhujun; Liao, Yanqiang; Cao, Yaxin; Li, Dongmei; Deng, Ningbo; Lei, Yeyan; Long, Xuanhui; Shen, Chenguang; Xu, Rui (Frontiers in Microbiology, 2024)
BackgroundPrevious microbiological investigations have demonstrated a significant correlation between Corynebacterium kroppenstedtii complex (CKC) infection and mastitis. Recent studies have confirmed the existence of the CKC, with Corynebacterium parakroppenstedtii (C. parakroppenstedtii) identified as the primary infectious agent. Examining the incidence of CKC in cases of severe non-lactational mastitis, alongside the clinical characteristics of infected patients, as well as evaluating the drug sensitivity testing protocols for CKC, can provide a more robust foundation for the diagnosis and treatment of CKC infections.MethodsData regarding the diagnosis and treatment of non-nursing patients with severe mastitis who underwent surgical intervention were extracted from the hospital’s electronic medical record system. Additionally, drug susceptibility tests were conducted on 15 strains of CKC isolated from mammary abscesses as well as DSM 44385 model strains. The effects of β-NAD and Tween80 (TW80) on the antibiotic susceptibility test by AGAR dilution and micro broth dilution were analyzed.ResultsIn this study, C. parakroppenstedtii accounted for 80% (12/15) of the isolates, while Corynebacterium pseudokroppenstedtii made up 13.3% (2/15), and Corynebacterium kroppenstedtii was identified in only 6.7% (1/15) of the cases. There were significant differences in age at first delivery (p < 0.001), prolactin (p < 0.001), CRP (p < 0.05), WBC (p < 0.05), and NEUT (p < 0.05) between CKC positive group and CKC negative group. In the AGAR dilution test, the addition of β-NAD only caused acceptable differences in penicillin G and ciprofloxacin but did not affect 12 antibiotics. There are 14 drugs with good coincidence rates (92.9%) in the micro broth dilution method and agar dilution method without the addition of β-NAD. The addition of 0.05% (v/v) TW80 resulted in all strains being resistant to penicillin G. Daptomycin is not suitable for the micro broth dilution method.ConclusionElderly primiparas with high prolactin levels have a higher risk of CKC infection. The micro broth dilution method is not applicable for EUCAST drug susceptibility testing for CKC and there is no suitable drug susceptibility evaluation procedure for daptomycin against CKC.